O017/#479 Germline pathogenic variants in DNA repair genes and endometrial cancer risk. (4th December 2022) - Gordhandas, Sushmita; Rios-Doria, Eric; Cadoo, Karen; Catchings, Amanda; Maio, Anna; Kemel, Yelena; Manning-Geist, Beryl; Sia, Tiffany; Roche, Kara Long; Leitao, Mario; Mueller, Jennifer; Makker, Vicky; et al.
Abstract : Objectives: We sought to determine the prevalence of germline pathogenic variants (gPVs) in unselected patients with endometrial cancer (EC), determine whether these gPVs were biallelic alterations, and define associations with clinicopathologic features. Methods: Germline assessment of ≥76 genes was performed in patients with EC undergoing clinical tumor-normal MSK-IMPACT (Integrated Mutation Profiling of Actionable Cancer Targets) sequencing from 1/2015–6/2021. Molecular subtypes were assigned using immunohistochemistry and somatic sequencing. In ECs with gPVs, biallelic alterations were identified through analysis of loss-of-heterozygosity and somatic PVs. Clinicopathologic variables were compared. Results: Of 1625 patients, 216 (13%) had gPVs. Compared to patients without gPVs, gPV patients were younger, more likely to self-identify as White, less obese, and had more endometrioid/clear cell vs. serous/carcinosarcoma histologies (p<0.05). 231 gPVs were identified in 35 genes—75 (32%) in high-penetrance, 39 (17%) in moderate-penetrance, and 117 (51%) in low/recessive/uncertain-penetrance genes. Seventy-four (32%) of 231 were biallelic. For ECs with high-penetrance gPVs, 63% (47/75) were biallelic, primarily affecting mismatch repair (MMR) and homologous repair (HR) genes, including novel HR genes RAD51D (2/2) and PALB2 (2/3) in addition to BRCA1 (10/10) and BRCA2 (6/11).Among all ECs, 552 (34%) were copy number (CN)-low, 514 (32%) CN-high, 413 (25%) microsatellite instability (MSI)-high, 106 (7%) POLE, and 40 (2%) unclassifiable. MSI-high and CN-high ECs were more likely to have biallelic gPVs (p<0.001; figure 1 ). Conclusions: Thirteen percent of patients had gPVs; 63% of high-penetrance gPVs potentially drove cancer development, supporting the utility of germline assessment given implications for treatment, cancer prevention, and at-risk relatives.